Phylogenetic systematics of egg-brooding frogs (Anura: Hemiphractidae) and the evolution of direct development - Castroviejo-Fisher, Santiago; Padial, José M. Jr.; de La Riva, Ignacio; Pombal, Jr., José P.; Silva, Helio R. Da; Rojas-Runjaic, Fernando J. M.; Medina-Méndez, Esteban; Frost, Darrel R. (Zootaxa, 2015)
Egg-brooding frogs (Hemiphractidae) are a group of 105 currently recognized Neotropical species, with a remarkable diversity of developmental modes, from direct development to free-living and exotrophic tadpoles. Females carry their eggs on the back and embryos have unique bell-shaped gills. We inferred the evolutionary relationships of these frogs and used the resulting phylogeny to review their taxonomy and test hypotheses on the evolution of developmental modes and bell-shaped gills. Our inferences relied on a total evidence parsimony analysis of DNA sequences of up to 20 mitochondrial and nuclear genes (analyzed under tree-alignment), and 51 phenotypic characters sampled for 83% of currently valid hemiphractid species. Our analyses rendered a well-resolved phylogeny, with both Hemiphractidae (sister of Athesphatanura) and its six recognized genera being monophyletic. We also inferred novel intergeneric relationships [((Cryptobatrachus, Flectonotus), (Stefania, (Fritziana, (Hemiphractus, Gastrotheca))))], the non-monophyly of all species groups previously proposed within Gastrotheca and Stefania, and the existence of several putative new species within Fritziana and Hemiphractus. Contrary to previous hypotheses, our results support the most recent common ancestor of hemiphractids as a direct-developer. Free-living aquatic tadpoles apparently evolved from direct-developing ancestors three to eight times. Embryos of the sister taxa Cryptobatrachus and Flectonotus share a pair of single gills derived from branchial arch I, while embryos of the clade including the other four genera have two pairs of gills derived from branchial arches I and II respectively. Furthermore, in Gastrotheca the fusion of the two pairs of gills is a putative synapomorphy. We propose a revised taxonomy concordant with our optimal topologies.